1996
DOI: 10.1136/jme.22.5.273
|View full text |Cite
|
Sign up to set email alerts
|

The legislation of active voluntary euthanasia in Australia: will the slippery slope prove fatal?

Abstract: At 2.00 am on the morning of May 24, 1995 the Northern Territory Legislative Assembly Australia passed the Rights of the Terminally Ill Act by the narrow margin of 15 votes to 10. The act permits a terminally ill patient of sound mind and over the age of 18 years, and who is either in pain or suffering, or distress, to request a medical practitioner to assist the patient to terminate his or her life. Thus, Australia can lay claim to being the first country in the world to legalise voluntary active euthanasia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The results showed that, while there was a somewhat larger percentage of nurses who stated that a law allowing euthanasia should not be allowed under any circumstances (26% versus 20%), and a 20% (17)(18)(19)(20)(21)(22) Not applicable Only if the patient is over a certain age. 6% (5-7) 7% (6)(7)(8)(9) corresponding lower percentage of nurses endorsing each condition, the pattern of results was very similar to that of the full sample. There were 210 (17%) who wrote an answer to "specify any other condition".…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The results showed that, while there was a somewhat larger percentage of nurses who stated that a law allowing euthanasia should not be allowed under any circumstances (26% versus 20%), and a 20% (17)(18)(19)(20)(21)(22) Not applicable Only if the patient is over a certain age. 6% (5-7) 7% (6)(7)(8)(9) corresponding lower percentage of nurses endorsing each condition, the pattern of results was very similar to that of the full sample. There were 210 (17%) who wrote an answer to "specify any other condition".…”
Section: Resultssupporting
confidence: 58%
“…There have been active euthanasia bills tabled in one state (South Australia in 1996) and two territory parliaments (Australian Capital Territory in 1993, 1995 and 1997 and Northern Territory in 1995).1-6 However, the only jurisdiction which has legalised AVE is the Northern Territory with its Rights of the Terminally Ill Act 1995. 7 The conditions of this act are summarised in table 1. This legislation was passed in May 1995 but was only in force for a brief time from July 1996 to March 1997.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there was a sixth basis for opposition, “opposed to Aboriginal cultural traditions”, which is context‐specific relating to the high proportion of Aboriginal people in the Northern Territory. The second most frequent argument, a variant of the “slippery slope” argument, was also highlighted in academic commentary at the time (Kerridge & Mitchell ).…”
Section: The Rise and Demise Of The Northern Territory Legislationmentioning
confidence: 95%
“…In 1995, Australia made international history as a forerunner for legalising assisted dying when, “after 3 months of lobbying(and) a raucous, nationwide debate” (Magnusson :61), the Northern Territory Legislative Assembly passed the world's first assisted dying legislation (Singer ; Kerridge & Mitchell ; Plattner ; Funk ). This was all the more remarkable as it was introduced at a time of a conservative administration led by Country Liberal Party Chief Minister, Marshall Perron, with the Chief Minister introducing the legislation, albeit as a private member's bill.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the autonomy supporters oblige a decision making by the patient's family members or by the court, as patient's representatives, in such a case that the patient is not able to autonomic thinking [15]. According to Kerridge and Kennth [16], if we assist a terminal patient, we should also respect the will of a patient who is not terminally ill but who is suffering from pain or a chronic disease, or who is found in a situation of loneliness and depression. It is common that one of the most necessary and tough criteria in this topic is that the patient would be terminally ill. Why this criterion among all others was chosen?…”
Section: Euthanasia -Ethical Dilemmasmentioning
confidence: 99%